Do Stepping Stone Jobs exist? Early Career Paths in the Medical Profession - Gerard J. van den Berg; Anders Holm; Jan C. van Ours (Tinbergen Institute, 1999)
In the Netherlands, students who want to become a medical specialist have toenrol in a training program which is in limited supply. During the search for aposition as trainee (or junior medical specialist), they may accept atemporary job as a medical assistant. We use a micro data set to investigatewhether such work experience increases the probability of becoming juniormedical specialist. To deal with selectivity, we simultaneously model thetransitions from unemployment to trainee, from unemployment to medicalassistant, from medical asistant to trainee and from medical assistant tounemployment. We find that a job as medical assistant helps to become a medicalspecialist.
Keywords: J64; C41; I21; 330; job search; multivariate duration models; hazard rate; education; university; treatment effect; Ärzte; Karriereplanung; Erwerbsverlauf; Niederlande